AKIBAT HUKUM ADANYA MISLEADING INFORMATION PADA PROSPEKTUS DI TINJAU DARI HUKUM PASAR MODAL - Hendra Jaya, Ade; Gatrawan, I Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2013)
This paper shall be entitled as “Legal Implication of Misleading Information towards Prospectus (Stock Market Regulatory Perspective)”. This paper shall aim on the investigation of the existing legal implication towards the untrue information provided for the prospectus within the general offering of an enterprise in its go public circumstances. Method of research utilized shall be normative legal research. Misleading information or untrue information shall be the the act of giving fallacy, partially true, incomplete or any other omission of acts of material information transfer which purported misleading information which is highly discouraged upon the principle of disclosure. Legal consequences of the misleading information in the prospectus will be subject to administrative sanctions.
Keywords: misleading information, prospectus, stock market, disclosure